2022
DOI: 10.1007/s00240-022-01360-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of TRPV5, CASR, and CALCR genetic variants with kidney stone disease susceptibility in Egyptians through main effects and gene–gene interactions

Abstract: Kidney stone disease (KSD) represents an urgent medical problem because of increasing its prevalence. Several functional polymorphisms in genes involved in the renal handling of calcium were associated with KSD pathogenesis. Among those, the rs4236480 of transient receptor potential vanilloid member 5 (TRPV5) gene, the rs1801725 of calcium-sensing receptor (CASR) gene, and the rs1801197 of calcitonin receptor (CALCR) gene appear to be of great importance. Due to the scarce data on the Egyptians, this study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Thoroughly reviewed in Dai et al (2010), Nishimura et al (2012), and Nilius and Voets (2013) TRPV5 Kidney stone (LOF) Khaleel et al, 2015;Oddsson et al, 2015;Wang et al, 2017;Ali et al, 2022 TRPV6 Chronic pancreatitis (LOF) Masamune et al, 2020;Zou et al, 2020 Transient neonatal hyperparathyroidism (LOF) Burren et al, 2018;Suzuki et al, 2018Suzuki et al, , 2020Yamashita et al, 2019;Almidani et al, 2020;Mason et al, 2020 Kidney stone (GOF) Inherited cardiac conduction defects, including progressive familial heart block type 1 (GOF), childhood atrioventricular block Kruse et al, 2009;Liu et al, 2010;Daumy et al, 2016;Syam et al, 2016;Xian et al, 2018;Janin et al, 2019;also Bassi et al, 2000;Sun et al, 2000 TRPML3 Varitint-waddler (Va) deafness (GOF) (in mice) Xu et al, 2007;Cuajungco and Samie, 2008;Nagata et al, 2008 TRPP2 Autosomal dominant polycystic kidney disease (LOF) Mochizuki et al, 1996;Wu and Somlo, 2000 GOF, gain of function; LOF, loss of function.…”
Section: Trpa1mentioning
confidence: 99%
“…Thoroughly reviewed in Dai et al (2010), Nishimura et al (2012), and Nilius and Voets (2013) TRPV5 Kidney stone (LOF) Khaleel et al, 2015;Oddsson et al, 2015;Wang et al, 2017;Ali et al, 2022 TRPV6 Chronic pancreatitis (LOF) Masamune et al, 2020;Zou et al, 2020 Transient neonatal hyperparathyroidism (LOF) Burren et al, 2018;Suzuki et al, 2018Suzuki et al, , 2020Yamashita et al, 2019;Almidani et al, 2020;Mason et al, 2020 Kidney stone (GOF) Inherited cardiac conduction defects, including progressive familial heart block type 1 (GOF), childhood atrioventricular block Kruse et al, 2009;Liu et al, 2010;Daumy et al, 2016;Syam et al, 2016;Xian et al, 2018;Janin et al, 2019;also Bassi et al, 2000;Sun et al, 2000 TRPML3 Varitint-waddler (Va) deafness (GOF) (in mice) Xu et al, 2007;Cuajungco and Samie, 2008;Nagata et al, 2008 TRPP2 Autosomal dominant polycystic kidney disease (LOF) Mochizuki et al, 1996;Wu and Somlo, 2000 GOF, gain of function; LOF, loss of function.…”
Section: Trpa1mentioning
confidence: 99%
“…Studies have reported that CALCR plays a crucial role in maintaining quiescence in muscle stem cells [ 10 ]. CALCR gene polymorphisms is involved in calcium urolithiasis in Russian population [ 11 ] and kidney stone disease in Egyptians [ 12 ]. Additionally, CALCR expression in the medial amygdala is associated with social contact of females [ 13 ].…”
Section: Introductionmentioning
confidence: 99%